1986
DOI: 10.1152/jappl.1986.60.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Forced oscillatory impedance of the respiratory system at low frequencies

Abstract: Respiratory mechanical impedances were determined during voluntary apnea in five healthy subjects, by means of 0.25- to 5-Hz pseudo/random oscillations applied at the mouth. The total respiratory impedance was partitioned into pulmonary (ZL) and chest wall components with the esophageal balloon technique; corrections were made for the upper airway shunt impedance and the compressibility of alveolar gas. Neglect of these shunt effects did not qualitatively alter the frequency dependence of impedances but led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 0 publications
3
68
0
2
Order By: Relevance
“…FOT and interrupter technique both measure R rs , which includes additional resistances of lung and thoracic tissue. Table 1 shows summarized and rounded estimates for fractions of flow resistance from studies on healthy individuals, in which measurements were performed during spontaneous breathing through the mouth at FRC and V T in the sitting position~Bachofen, 1966; Barnas et al, 1992;Ferris, Mead, & Opie, 1964;Hantos, Daróczy, Suki, Galgoczy, & Csendes, 1986;Hyatt & Wilcox, 1961;Jaeger & Otis, 1964;McIlroy, Mead, Selverstone, & Radford, 1955!. 3 The estimates were obtained by different combinations of these techniques with more invasive methods such as the esophagus balloon catheter or pressure recording via a needle inserted into the extrathoracic part of the trachea. Most authors reported a considerable interindividual variation in estimates, probably due to anatomic differences.…”
Section: Comparison Between Methods Of Airflow Resistance Measurementmentioning
confidence: 99%
“…FOT and interrupter technique both measure R rs , which includes additional resistances of lung and thoracic tissue. Table 1 shows summarized and rounded estimates for fractions of flow resistance from studies on healthy individuals, in which measurements were performed during spontaneous breathing through the mouth at FRC and V T in the sitting position~Bachofen, 1966; Barnas et al, 1992;Ferris, Mead, & Opie, 1964;Hantos, Daróczy, Suki, Galgoczy, & Csendes, 1986;Hyatt & Wilcox, 1961;Jaeger & Otis, 1964;McIlroy, Mead, Selverstone, & Radford, 1955!. 3 The estimates were obtained by different combinations of these techniques with more invasive methods such as the esophagus balloon catheter or pressure recording via a needle inserted into the extrathoracic part of the trachea. Most authors reported a considerable interindividual variation in estimates, probably due to anatomic differences.…”
Section: Comparison Between Methods Of Airflow Resistance Measurementmentioning
confidence: 99%
“…The most common is to excite the respiratory system with small amplitude pseudorandom noise using a loud-speaker. 9 While straightforward, this technique has several technical and clinical drawbacks. It requires highperformance subwoofer speakers relatively free of harmonic distortion.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 Finally, this approach requires considerable subject cooperation. Awake subjects require training to achieve the necessary prolonged periods of apnea and respiratory muscle relaxation, 9 which makes the method impractical for routine use in patients with impaired lung function. In anesthetized and paralyzed patients, this technique usually requires temporary interruption of artificial ventilatory support.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that extrathoracic airway wall structures have negligible impact on the measurement of the tissue properties in infants using the LFOT, after correction for the parallel shunt imposed by the equipment deadspace and face mask, and when firm support of the cheeks and jaw are maintained throughout the measurement (13). This can be explained by the relative rigidity of the nasal passages compared with the oral structures, and also by the similar frequency dependencies of Z rs and the upper airway wall impedance (10) in the low-frequency region. On the other hand, inclusion of the nasal passage in the impedance measurement exerts a more marked effect on airway resistance and inertance (13), although to a lesser extent than observed during forced oscillations at higher frequencies (27).…”
Section: Discussionmentioning
confidence: 93%
“…At low frequencies, the resistance and reactance decrease nearly hyperbolically with increasing frequency. At higher frequencies, the tissue properties become less important and the largely frequencyindependent airway properties of resistance and inertance dominate (10). Variables representing the mechanical properties of the airways (resistance and inertance) and the tissues (resistance or "damping" and the elastance) can be obtained by fitting a model to the impedance spectra (9).…”
mentioning
confidence: 99%